2006
DOI: 10.1260/136943306779369446
|View full text |Cite
|
Sign up to set email alerts
|

Deterioration of FRP-to-Concrete Bond under Failure Loading

Abstract: Characteristics of FRP-to-concrete bond are observed to deteriorate under cyclic loads. Deterioration has been observed under load conditions which result in a stress range in the bonded FRP of only 4% of the material capacity. Current design recommendations and “accepted practice” often neglect this detrimental effect. The clear effects of bond deterioration under fatigue loading are demonstrated for moderate-scale laboratory specimens and in full-scale specimens recovered from a forty-year old interstate hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 10 publications
0
7
0
2
Order By: Relevance
“…Some FRP materials are additionally susceptible to creep owing to sustained loads and adhesive bondlines are susceptible to damage from cyclic (fatigue) loads. 11 Research efforts associated with the use of FRP materials in concrete infrastructure offer some relevant guidance as to the effect of typically experienced environmental and mechanical loading conditions. When used in conjunction with a steel substrate, some additional environmental protection may be accorded the CFRP by the presence of fireproofing, topcoat or finishing systems.…”
Section: Environmental Exposure Creep and Fatigue Behaviourmentioning
confidence: 99%
“…Some FRP materials are additionally susceptible to creep owing to sustained loads and adhesive bondlines are susceptible to damage from cyclic (fatigue) loads. 11 Research efforts associated with the use of FRP materials in concrete infrastructure offer some relevant guidance as to the effect of typically experienced environmental and mechanical loading conditions. When used in conjunction with a steel substrate, some additional environmental protection may be accorded the CFRP by the presence of fireproofing, topcoat or finishing systems.…”
Section: Environmental Exposure Creep and Fatigue Behaviourmentioning
confidence: 99%
“…The fatigue performance of the FRP-strengthened concrete structures has been studied, which reveals the basic mechanical principles under fatigue loading (Huang et al, 2017;Wight and Erki, 2003). As reported, FRP materials exhibit excellent fatigue behavior (Kim and Heffernan, 2008;Peng et al, 2016;Siddika et al, 2019), and the failure often initiates from the debonding of FRP materials (Deng et al, 2015;Harries et al, 2006;Wahab et al, 2012) or the fracturing of steel reinforcements (Aidoo et al, 2004;Papakonstantinou et al, 2001). Several models have been proposed to predict the fatigue life of the reinforced concrete (RC) structures strengthened with FRP composites (Aidoo et al, 2004;Al-Qaralleh and Toutanji, 2018) and some studies focused on the postfatigue behaviors of the FRP-strengthened structures (Sena-Cruz et al, 2012;Song and Hou, 2017).…”
Section: Introductionmentioning
confidence: 93%
“…To fully utilize the capacity of the FRP composites, a prestressed method was proposed and has been regarded as an excellent option (Triantafillou et al, 1992; Wight et al, 2001; Zhou et al, 2018). Extensive investigations were carried out on the strengthening effects (Garden et al, 1998; Yang et al, 2009), bonding behaviors (Aydin et al, 2016; Harries et al, 2006; Neale et al, 2006), and anchoring effects (Mohee et al, 2016; Nanni et al, 1996) of the concrete members strengthened with prestressed FRP. Numerical and theoretical methods were also regarded as effective methods to conduct the research (Baky et al, 2010; Carpinteri et al, 2009; Chen et al, 2016; Chen and Teng, 2001; Sturm et al, 2019; Valipour and Foster, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…However, other studies (Masoud et al, 2001;Breňa et al, 2005;Harries and Aidoo, 2005;Harries, 2005) reported that there is no corresponding increase in the fatigue life. Thus, it is believed that improvement in fatigue performance is only affected as long as the FRP is adequately bonded to the concrete.…”
Section: Introductionmentioning
confidence: 93%